(untitled) (Research, Society and Development, 2025)
Childhood vaccination is one of the most effective public health prevention strategies and represents an important tool for reducing infant morbidity and mortality. The objective of this article is to present an experience report which aimed to develop educational actions in health focused on promoting childhood vaccination in the Kainã Village, integrating traditional indigenous knowledge to strengthen intercultural dialogue and access to health. The methodology used was qualitative, descriptive, and exploratory, based on participant observation, workshops, and educational activities conducted in partnership with indigenous leaders and nursing students. The study was limited to the Kainã Village, located in the Amazon region, where access to immunization is influenced by sociocultural, geographic, and logistical factors. The results showed that during the activities developed with educational and playful dynamics about the importance of childhood vaccination, promoting the active participation of children and their families, this approach facilitated the understanding of the benefits of vaccines and generated an environment of trust and mutual respect between the community and health professionals. It can be concluded that the extension workers acted as mediators between scientific knowledge and traditional wisdom, using accessible language and visual strategies that stimulated interest and learning.